Benefit of Preoperative Temporal Bone CT for Atraumatic Cochlear Implantation. Issue 3 (March 2018) - Karkas, Alexandre; Champfleur, Nicolas Menjot de; Uziel, Alain; Mondain, Michel; Puel, Jean-Luc; Venail, Frédéric
Abstract : Hypothesis: Evaluate the benefit of preoperative surgical planning using computed tomography (CT) for atraumatic cochlear implantation. Background: The surgical technique has a direct impact on hearing and structure preservation. Much interest has been given to depth of electrode insertion. We focused on electrode diameter depending on exposure of round window membrane (RWM) as calculated on preoperative CT. Methods: Measurements were calculated radiologically and anatomically on 10 temporal bones. Results were compared with CT scans of a control population. Thereafter, preoperative CT scan measurements were applied to seven additional temporal bones that underwent cochlear implantation with the insertion of two electrodes of different diameters (14 implantations) to validate radiological analysis. Results: RWM size was 1.5 ± 0.2 mm on CT and 1.2 ± 0.2 mm during dissection; posterosuperior bony overhang of round window niche was 1.1 ± 0.1 mm on CT and 1.3 ± 0.2 mm during dissection. There was no statistically significant difference between radiological and anatomical measurements and between radiological measurements of cadaveric temporal bones and control population ( p > 0.05 for both). Also, preoperative surgical planning was reliable in the seven temporal bones implanted with two electrode types (accuracy 93%, sensitivity 85.7%, specificity 100%) yielding no damage to intracochlear structures. Conclusion: Difficulties to access RWM could be predicted on preoperative CT of temporal bones and control population, which correlated well with anatomical dissections and surgical findings during cochlear implantation. According to CT planning, electrode insertion through RWM was feasible in most patients, with or without drilling posterosuperior bony overhang of round window niche. Promontory cochleostomy could be recommended when electrode apical diameter exceeded maximal RWM exposure. There was no case of intracochlear trauma on microdissections.